THE MEANING OF SWEAR WORDS IN CRANK AND CRANK 2: HIGH VOLTAGE MOVIES - SATRIA PERMANA, BUDHI (Language Horizon: Journal of Language Studies, 2013)
Abstrak Ada dua hal yang sangat sakral pada tingkah laku. Pertama adalah perilaku yang tabu dan kata-kata yang tabu atau kata-kata umpatan. Kata-kata tabu atau kata-kata umpatan adalah kata kata yang menghina yang diucapkan untuk mengekspresikan kebencian, menunjukkan kemarahan, atau hanya sebagai pemanis kata. Kata-kata umpatan juga bias digunakan sebagai intimidasi seperti layaknya sebuah humor. Studi ini tertuju untuk menganalis kata-kata makian yang muncul didalam film.Peneliti menggunakan film aksi Amerika Crank dan Crank 2:High Voltage sebagai sumber data didalam penelitian. Peneliti tertarik untuk mencari bentuk dan arti dari kata-kata makian yang diucapkan oleh semua karakter di dalam film ini dan juga peneliti tertarik untuk menganalisis dalam konteks apa kata-kata makian tersebut muncul pada film tersebut. Dengan mengidentifikasi dua masalah tersebut, peneliti mampu untuk mendapat pengetahuan tentang bentuk semantic relasi dari kata-kata makian dan dalam konteks apa kata-kata makian tersebut diucapkan. Dalam melakukan penelitian ini, peneliti menggunakan metode penelitian deskriptif kualitatif untuk menganalisis data. Karena penelitian ini adalah kualitatif maka peneliti menjadi instrument kunci untuk mengumpulkan data.Data diambil dengan melihat film, lalu data diklasifikasikan berdasarkan bentuk semantic relasi. Peneliti juga menganalisis dan mencari konteks social pada kata-kata makian yang diucapkan oleh semua karakter untuk menjawab pertanyaan kedua.Pada akhirnya, data diubah melalui analisis yang merujuk kefungsi bahasa berdasarkan teori Keith Allan. Hasil dari penelitian menunjukkan bahwa kata-kata makian yang dilontarkan oleh karakter-karakter dari film Crank dan Crank 2: High Voltage terpengaruh oleh berbagai macam situasi dan kondisi. Peneliti juga mengkonklusikan bahwa pemahaman dari arti kata-kata makian tersebut sangat berpengaruh untuk membantu penonton memahami konteks dari percakapan-percakapan dalam film tersebut. Kata Kunci: Arti, Kata-kata Makian, Film. Abstract There are two things that are sacred in human behavior. First is taboo acts and taboo words or swear words. Taboo words or swear words are obscene words which is spoken to express hatred, show anger, or just as a sweetener words. It can also be used as intimidation as well as humor. This study is intended to analyze the swear words that appear in movie The researcher uses a american action movies Crank and Crank: 2 High Voltage movies as the source of data in his research. The researchers is interested to find out the form and meaning of swear word that uttered by all of character in this movie and also the reseacher interested to analyze in what context swear words occur in these movie. By identifying these two problems, the reseacher is able to get the knowledge of the form of semantics relations from swear words and in what context swear words uttered.In conducting this research, the researcher uses a descriptive qualitative research method to analyze the data. Since this research is qualitative, then the researcher becomes the key instrument to collect and analyze the data. the data are taken by watching the movie, after that the data are classified based on semantic relation forms. The researcher also analyzes and finds out the social context of swear words which are uttered by all of characters to answer the second statement problem. Finally the data are transformed through the analysis of language function based on Allan’s theory.The result of the analysis show that the the use of swear words that uttered by characters in Crank and Crank 2:High Voltage movies is influenced by a variety of situations and conditions. The researcher also conclude that the comprehesion of the meaning of swear words is very influential to help the audience to understand the context of the conversation Keywords: Meaning, Swearwords, movies INTRODUCTION . Human are social beings. Every individual needs other to complete their life. Every individual or people have ability to talk with each other which could be considered as performing communication. By doing communication we are able to deliver what we want to express. In this case, people communicate with the other by using language. Language contains of words which are pronounced, combined into sentence and understood by community. In general, people use language to communicate with the other. With language we can submitideas,messages, purposes , feelings and opinionsto the people. Language also have three basic functions. It is an informative language function. It is used when we make an information, give a statement, or describe something. Second, it is an expressive language function. It can report feelings or attitudes of the writer (or speaker), or of the subject, or evokes feelings in the reader (or listener). The example of this function can be found in daily activities conversation, for example : “Wow, what amazing picture”. Third, it is a directive language function. It is used when language is used for the purpose of causing (or preventing) overt action. The example of this function can be found in daily activities conversation, for example is please close the window One of the language function is to express the feelings like loneliness, happines, sadness, anger etc. Swear words are identical with harshness. So, swear words are usually uttered by people who have a bad attidute or bad habbit. Swear words are one of form expression that appear from these fellings. Swearing and cursing are modes of speech existing in all human languages. They perform certain social and psychological functions. So why do people swear? Why does using a swear word make us feel better? How do we choose which word we use? Swearing is usually used when someone suddenly gets angry. According to Andersch (in Liedlich, 1973:108), people should not use the obscene words to swear because the words are viewed as indecent and offensive.Besides, Crystal (1987:10) defines that swearwords are used to express their feeling, especially when one is in angry. The feeling can be anger, indignation, annoyance, intimacy, or joke. Related to the explanation above, swearword is a word or some words that produce swear meaning that used by people when they are angry, want to convince something, to show surprise or make a joke. Swearing is beneficial in ways that people may underestimate or take for granted. Swearing is often cathartic — it often frees us from the feelings of anger or frustration when we hold and allows expression for them. It can also be a useful substitute to physical violence (who would rather be punched out than to withstand being sworn at?). Swear words can also be used in a more positive manner, in the form of jokes and humor, sex talk, storytelling, self-deprecation or even social commentary. According to Erick Partridge (1984 :144) thepurpose of the swearwords are to insult, to mock,to curse and also to mock somebody with obscene words. Actually, many kinds of swearwords are forbidden to appear in any conversations in both formal and informal situation. However, people recently often use many swearwords in their daily life. Imagine when you want to emphasize how great you feel something is, a swear word emphasizes the positive feelings you have for that object, situation, person or event (“This concert is fucking awesome!”). Sure, we could just say “This concert is awesome,” but the addition of the swear word emphasizes the emotional reaction we have toward it — and easily conveys that emotional reaction to others. Therefore the researcher curious about the semantic properties of swear words that occured in this movie. And also the researcher want to analyze thecontext of swearwords in their conversation. . This movie is interesting to be analyzed because it illustrates about a hitman named Chev Chelios who have had problems with another gang. The story is told with coarse language, adult, crazy, vulgar and full of cruelty. Mark Neveldine and Brian Taylor are the director and the script writer, they try to describe the dark side of the gangster world in the form of offensive language that appeared in the United States Crank and Crank 2 : High Voltagemovies is a movies that contains a lot of swear vulgar, rough, sinful, and adult words. In fact this film (Crank) also gets a reward from MSN movies award as the most offensive male character that starred by Jason Statham. Since themovie has a lot of swear words, the audience will face a conversation between Chev Chelios and his enemies that contain many swear words. The stories starts with Chev Chelios that framed by Ricky Verona. Chev Chelios has been chased by many mafias because of his reputation as a first-class assassin The researcher wants to analyze the swear words that are spoken by main characters on this movie with the theory of semantics. Because with semantics theory we can understand the meaning of swear words that are spoken by main characters that always speak about swear words in any condition and situation with different variations of swear words METHODOLOGY Research Design To make a research, we should to make a research design to design a framework of research itself. Based on Donald ( 2002: 426), the research design is the research’s plan of how to proceed to gain an understanding of some group or some phenomenom in natural setting. The qualitative research design is compatible in the study since the form of data is in the words, phrases, clauses, and sentences rather numbers. The data taken from Crank and Crank 2 : High Voltage movies scripts.As qualitative research, this study is concerned with characteristic of the qualitative research, such as natural setting, human instrument, inductive data, analysis, descriptive discussion and focus more on procces than result. Since the objectives of this research are to understand and to recognize the types, sources, styles and functions of semantic relation and also to understand the social context of swearwords that uttered in Crank and Crank 2 : High Voltage movies, the researcher report it in form of descriptive research.In the qualitative research, the human investigator is the primary instrument for gathering and analyzing of data. Since this research is carried out in discussing the swearwords in conversation, the researcher needs to observe by collecting the script of these movie from the internet. Then he chooses type script that contain swearwords. The researcher collects the data via observing and understanding those script as an outsider observer.The data collections which are coleected in this qualitative research are not in form of numbers, but words, phrases, clauses and sentences. Therefore, the findings are discussed and analyzed in the term of words, phrases, clauses, and sentences. The statistical data analysis is not applied in this study. Finally the qualitative research focuses on the process more than the result, which implies that it is much better in investigating the object of research in detail and accurate within the process. Research Instruments Research instrument is a tool or equipment utilizied in the collcting of data. Because it is qualitative research, the researcher himself is the primary instrument for gathering and analyzing the data. The researcher spends a great of time to observe and take an active participation by reading intensively, understanding, browsing, selecting, analyzing and taking a notes of swearwords in those movies. Because via those efforts,the data required can be taken and selected. The researcher involves directly in analyzing the data and placed as an observer. Data Collection Technique The researcher collected the data by observation method. The researcher use non-participant method. Based on Donald (2002: 274) Non participant method or direct, observation is where data are collected by observing behaviour without interacting with the participantsThe researcher tried to find out the scripts of Crank and Crank 2 : High Voltage movie through http://subscene.com then researcher was looking for the desired movie. There were many version of scripts that come from a variety of languages. Then the researcher took english script version. After that the researcher checked those scripts by watching the movies whether those scripts were valid or not. After obtaining the data from those sites, the researcher read the scripts again until the researcher understood the swearwords found in those scripts. Data Analysis Technique The process of analysis is using the interactive model, after the data collected, they are arranged systematically based on the problems of study. Then they are selected, which one is considered swearwords in the scripts. Next, after the data classified, the researcher answer the statement of problems by find outthe semantic relations form (find the synonym, polysemy, hypernym, hyponym and antonym form) of swearwords. Next, the researcher also analyzes and finds out the social context of swearwords which are uttered by all of character in those movies to answer the second statement of problems. And then, the data are transformed through the analysis of language function based on Allan’s theory. After the data are discussed and the findings are presented, the researcher draws and make the tentative conclusion of the study. After consulting the experts, the final conclusion and the finding of the study are presented, then the final is proposed. DATA ANALYSIS AND DISCUSSION In the analysis of data, the researcher found that not all swear words that appear in Crank and Crank 2: High voltage are pure swearwords. It can be seen in the data 6, 7, and 13. Although in the data 7 and 13 has a negative meaning, but the way of the speakers to uttering these words are not included as offensive language. These data can be considererd as euphemism that has a fuction as sweet talking. The researcher also found that the others data included in dysphemism category. In the data 1,2,3,5,10, and 12 has a negative meaning such as sense of dissapointment, insulting people, or show a hatred. In the data 4,8,9,11,and 14 also considered as swear words but has a different meanings with previous data such as show familiarity and attract the people. Table 1 List of Language Expression Type of language expression Data Language expression in details Meaning ORTHOPEMISM EUPHEMISM Data 6: FAGGOT To make a joke Data 7: JERK-OFF To mock person Data 13: TWAT To discredit person DYSPHEMISM Data 1: SHIT Synecdoche Sense of dissapointment Data 2: ASSHOLE Synecdoche Data 10: SUCKER Synecdoche To show hatred Data 12: BASTARD Synecdoche To discredit people Data 3: BITCH Euphemistic Dysphemism Used for people who is throughly disliked Data 4: NIGGER Euphemistic Dysphemism To show familiarity Data 5: ASS Euphemistic Dysphemism To show hatred Data 8: COCK Euphemistic Dysphemism To make a joke Data 11: MOTHERFUCKER Euphemistic Dysphemism To show familiarity Data 14: GODDAMN Euphemistic Dysphemism To attract people Data 9: DOG Dysphemistic Euphemism To show familiarity GRATITUTION May Allah be honored for His love and mercy, this journal can be complete. His deepest and most frankly gratitude is conveyed to: Lisetyo Ariyanti S.S., M.Pd, for the attention and advice for this journal CONCLUSIONS In line with the previous chapter, the conclusion of this research can be formulated based on the proposed research question. According to the study, the result of the analysis, the researcher can say that there are a lot of varietysemantic relation in swear words that appear in Crank and Crank 2: High Voltage. The researcher noticed that themost all of data taken including or has the meaning as swearwords (shit, asshole, bitch, nigger, faggot,cock, dog, sucker, motherfucker, bastard, ) and the rest has not a function as swear words (ass, twat and goddamn). The researcher also conclude that most of all characters uttering a swear words are to insulting a people or show a hatred (negative purpose) and the rest has a function as sign of friendship or has a function as a joke.(positive purpose) SUGGESTION Based on finding of this research described previously, there are several things that could be advised. For the author, in writing a script movie, they should noticed the choice word. The scriptwriter should choose word that are easy to understand so that the audience is able to understand the meaning of those words. And for researcher who want to research this field and interested in this study, suggested to use different data sources and use a same theory of Allan. The researcher should understand which is included swearwords and which are not. To make this thesis more perfectly, the criticism and suggestion from the readers are needed REFFERENCES Allan, Keith. 2006. Forbidden Words: Taboo and the Censoring Language. Cambridge : Cambridge University Press Crystal, David. 1987. The Cambridge Encyclopedia of Language. Cambridge: Cambridge University Press Denning, Keith.English Vocabulary Elements. Oxford : Oxford Univ. Press, 2007 Donald, Ary.Introduction to Research in Education. New York: Holt Richard and Winston, 2002 Fairman, Christoper. 2006. Fuck. Ohio : Ohio State Moritz College of Law Feldman, Laurie.Morphological Aspects of Language Processing. Lawrence Erlbaum, 1995 Hughes, G. 1991. Swearing: A Social History of Foul Language, Oath, and Profanity in English. New York: Blackwell Publishers. James, Carl. 1980. Contrastive Analysis. London: Longman Liedlich, Raymond D. 1973. Coming to the Term with Language: An Anthology. New York: John Wiley and Sons, Inc. Lyons, John. 1981. Language and linguistic and Introduction. Cambridge : Cambridge University Press Murphy, Lynne. 2003. Semantic Relation and the Lexicon. Cambridge : Cambridge University Press O’Grady, William. 1996. Contemporary Linguistic An Introduction. London : Longman Partrige, Eric. 1984. A Dictionary of Slang and Unconventional English. Cambridge : Cambridge University Press Pearsall, Judy. 2003. New Oxford Dictionary of English. Oxford : Oxford University Press Radford, Andrew. 1999. Linguistic: An introduction. Cambridge : Cambridge University Press Yule, George.2006. The Study of Language. Cambridge: Cambridge University Press https://sites.google.com/a/sheffield.ac.uk/all-aboutlinguistics/branches/pragmatics (accesed on Saturday, May 18th 2013 21.42) https://sites.google.com/a/sheffield.ac.uk/all-about-linguistics/what-is-linguistics (accesed on Thursday, May 16th 2013 02.14) https://sites.google.com/a/sheffield.ac.uk/all-about-linguistics/branches/semantics (accesed on Saturday, May 18th 2013 21.00) https://sites.google.com/a/sheffield.ac.uk/all-about-linguistics/what-is-linguistics (accesed on Wednesday, May 22nd 2013 17.16) http://www.eicar-international.com/definition-film.html ( accesed on May 9th 2013 09.15)